The remedium amoris in La dama boba of Lope de Vega: source of epistemology - Altamirano, Sebastián (2015)
The investigation focuses in analyze the variant of the greco-roman topic remedium amoris as a source of epistemology in the comedy La dama boba from Félix Lope de Vega. In this comedy appears a contrast between two feminine characters who are sisters, Nise y Finea, on having emphasize that the first one is an erudite woman, while the second one a silly lady. Nevertheless, the ignorance attributed to Finea will be reducing as she begins to love Laurencio and in this way the love will stop needing a remedy to turn in to the cure against the erudition lack. The investigation analyze by means of literary prescripts like the metaphor and the rhetorical ethos, the relevancy that has the love to alter a topic and to prevail like the best magister, the one that it teaches beyond its own field.